Diseño y desarrollo de una aplicación web de un modelo multicriterio hibrido fuzzy-ahp-topsis. (2024)
This undergraduate thesis aims to design and develop a web application as a tool for decision-making, using a hybrid multicriteria analysis methodology. The motivation behind choosing this topic is the need to provide an innovative instrument that contributes to decision-making in the industrial field concerning energy efficiency, in order to provide a deeper analysis of impacts on the technical, social, economic, and environmental aspects. The hybrid methodology of Fuzzy AHP TOPSIS allowed demonstrating in the pilot test the practicality, speed, and functionality of the application, yielding interactive analysis with the user for a broader view in the evaluated processes and assessing the influence of each criterion and sub-criterion in the prioritization of energy efficiency, providing the most suitable decision alternatives. In conclusion, the research evaluated the impact of developing the application as an innovative tool that offers a significant contribution in research, in social, economic, scientific, environmental, and industrial aspects.